2021
DOI: 10.1002/stc.2697
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of shape memory alloy energy dissipators for earthquake‐resilient structures

Abstract: Summary In this paper, a new shape memory alloy (SMA) damping device named confined superelastic dissipator (CSD) was examined. The proposed dissipator consists of a fused superelastic nickel‐titanium (NiTi) SMA bar as the functional kernel component encased in grout‐filled steel tube. The bar carries the axial load and dissipates energy through axial deformation while the steel tube and infill grout restrain the bar and precludes buckling in compression. First, theoretical derivations for the design of the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Since the SMAs are more readily available as small-diameter wires, most of earlier studies have used SMA wires to develop SMA-based seismic protection systems, leading to laboratory scale devices. There have been also a few experimental studies where large-diameter SMA bars were considered as a damper or bracing system in buildings (Asfaw and Ozbulut, 2021; Cao and Ozbulut, 2020; Miller et al, 2012). For enabling the anchorage of SMA bars in these systems, SMA bars commonly need to be machined or threaded.…”
Section: Introductionmentioning
confidence: 99%
“…Since the SMAs are more readily available as small-diameter wires, most of earlier studies have used SMA wires to develop SMA-based seismic protection systems, leading to laboratory scale devices. There have been also a few experimental studies where large-diameter SMA bars were considered as a damper or bracing system in buildings (Asfaw and Ozbulut, 2021; Cao and Ozbulut, 2020; Miller et al, 2012). For enabling the anchorage of SMA bars in these systems, SMA bars commonly need to be machined or threaded.…”
Section: Introductionmentioning
confidence: 99%
“…SMA is a material capable of experiencing significant strains and recover its original shape without experiencing residual strains. Since SMAs have high energy dissipation capacities and superelastic properties, they are ideal for applications under extreme loading such as earthquake (Alam et al, 2007a; Asfaw and Ozbulut, 2021) and impact (Gholipour and Billah, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have focused on resilience enhancement of structures by employing the superelastic shape memory alloy (SMA), 24,25 for example, bridges 26–28 . The effectiveness of the SMA regarded as the damping and re‐centering devices for structural response control has been demonstrated 29–32 . Several studies have revealed that combining the SMA device with isolators is particularly efficient for residual displacement mitigation 33–39 .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] The effectiveness of the SMA regarded as the damping and re-centering devices for structural response control has been demonstrated. [29][30][31][32] Several studies have revealed that combining the SMA device with isolators is particularly efficient for residual displacement mitigation. [33][34][35][36][37][38][39] Particularly, considering the advantages of the SMA as damping and re-centering components, several SMA-based isolators, which combine the superelastic SMA wire/cables with the traditional friction isolators, have been examined for performance improvement of structures, for example, the SMA-based pure-friction sliding bearing, [38][39][40][41][42][43][44] SMA-friction pendulum bearing, [45][46][47][48][49] which demonstrated the feasibility using the SMA device to enhance the structural seismic resilience.…”
Section: Introductionmentioning
confidence: 99%